Open-source sensor for measuring oxygen partial pressures below 100 microbars. - Mihkel Pajusalu; Cauê S Borlina; Sara Seager; Shuhei Ono; Tanja Bosak (PLoS ONE, 2018)
The ability to measure partial pressures of oxygen below 100 microbars and nanomolar dissolved oxygen concentrations in in situ laboratory systems benefits many fields including microbiology, geobiology, oceanography, chemistry, and materials science. Here, we present an easily constructible open-source design for a networked luminescence lifetime measurement system for in situ measurements in arbitrary laboratory containers. The system is well suited for measuring oxygen partial pressures in the 0-100 μbar range, with the maximum potentially usable upper range limit at around 10 mbar, depending on experimental conditions. The sensor has a limited drift and its detectability limit for oxygen is at 0.02 μbar for short timescale measurements. Each sensor can connect to a Wi-Fi network and send the logged data either over the Internet or to a local server, enabling a large number of parallel unattended experiments. Designs are also provided for attaching the sensor to various commercially available containers used in laboratories. The design files are released under an open source license, which enables other laboratories to build, customize, and use these sensors.